Aerodynamics of gliding flight in common swifts. - Henningsson, Per; Hedenström, Anders (Journal of Experimental Biology, 2011)
Gliding flight performance and wake topology of a common swift (Apus apus L.) were examined in a wind tunnel at speeds between 7 and 11 m s(-1). The tunnel was tilted to simulate descending flight at different sink speeds. The swift varied its wingspan, wing area and tail span over the speed range. Wingspan decreased linearly with speed, whereas tail span decreased in a nonlinear manner. For each airspeed, the minimum glide angle was found. The corresponding sink speeds showed a curvilinear relationship with airspeed, with a minimum sink speed at 8.1 m s(-1) and a speed of best glide at 9.4 m s(-1). Lift-to-drag ratio was calculated for each airspeed and tilt angle combinations and the maximum for each speed showed a curvilinear relationship with airspeed, with a maximum of 12.5 at an airspeed of 9.5 m s(-1). Wake was sampled in the transverse plane using stereo digital particle image velocimetry (DPIV). The main structures of the wake were a pair of trailing wingtip vortices and a pair of trailing tail vortices. Circulation of these was measured and a model was constructed that showed good weight support. Parasite drag was estimated from the wake defect measured in the wake behind the body. Parasite drag coefficient ranged from 0.30 to 0.22 over the range of airspeeds. Induced drag was calculated and used to estimate profile drag coefficient, which was found to be in the same range as that previously measured on a Harris' hawk.